ENGLISH LIGHT VERB CONSTRUCTIONS WITH THE VERB TAKE (Journal of Contemporary Philology, 2018)
This paper focuses on the English light verb constructions (LVC) with the light verb take. Theseare classified into four groups based on semantic criteria. In addition, the metaphorical extensions of the light verb take are discussed in detail  for each group. Examples sentences  with LVCs with take are  extracted from the  British  National Corpus  (BNC) and  are  thenanalyzed.  Theexpressive possibilities  of the  LVCs  are explored in comparison to the corresponding lexical verbs. This paper particularly aims to discover whether a relation of synonymy can always be established between a LVC and its corresponding lexical verb,  whether LVCs with take and  their corresponding lexical verbs can encode an aspectual opposition, and whether LVCs with take allow for  a  more  precise  expression compared to  the  corresponding lexical verbs. The qualitative analysis of the collected data is accompanied by a quantitative analysis.
Keywords: light-verb constructions; light verbs; deverbal nouns; metaphorical extensions